2007
DOI: 10.1002/qj.156
|View full text |Cite
|
Sign up to set email alerts
|

Case-study of a principal-component-based radiative transfer forward model and retrieval algorithm using EAQUATE data

Abstract: ABSTRACT:The objective of the paper is to apply a novel radiative transfer model and a physical retrieval algorithm to hyperspectral data taken during the European Aqua Atmospheric Thermodynamics Experiment (EAQUATE) campaign. A principal-component-based radiative transfer model (PCRTM) is used to calculate projection coefficients of the radiance spectrum onto a set of predefined empirical orthogonal functions (EOFs) and associated derivatives with respect to the state vector. Instead of fitting channel radian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…Aires et al (2002) found that for the IASI instrument, an EOF number of 30 for each of the three bands (or 90 total) will give the best compression/de-noising statistics. We have reached a similar conclusion in our studies here and in Liu et al (2007). These super channels essentially contain all the information content of 8461 IASI channels, while having 84 times less data volume.…”
Section: General Description Pcrtm Forward Modelsupporting
confidence: 90%
See 1 more Smart Citation
“…Aires et al (2002) found that for the IASI instrument, an EOF number of 30 for each of the three bands (or 90 total) will give the best compression/de-noising statistics. We have reached a similar conclusion in our studies here and in Liu et al (2007). These super channels essentially contain all the information content of 8461 IASI channels, while having 84 times less data volume.…”
Section: General Description Pcrtm Forward Modelsupporting
confidence: 90%
“…The CO profile EOFs are generated from the NCAR Mozart model (Kinnison et al, 2007). For the surface emissivity retrieval, we compress the surface emissivity into PC scores as well Liu et al, 2007). Since the spectral features of the surface emissivity are broad, there is no need to retrieve them at each channel frequency.…”
Section: Description Of a Super Channel Based Retrieval Algorithmmentioning
confidence: 99%
“…the principal components (PC) transform (e.g. Jolliffe, 2002), the use of which to reduce the dimensionality of the radiative transfer equation has been exemplified by Masiello and Serio (2004) and Liu et al (2007Liu et al ( , 2009). Today, forward models for IASI capable of computing PC scores directly are available (see, for example, Masiello and Serio, 2004;Liu et al, 2006;Matricardi, 2010), which could speed up the process of adapting the assimilation process for IASI PC scores.…”
Section: Introductionmentioning
confidence: 99%
“…The CC is used by the AIRS level 2 data processing algorithm and by the Joint Polar Satellite System (JPSS) Cross-track Infrared and Microwave Sounder Suite (CrIMSS) algorithm. At NASA Langley Research Center (LaRC) [5,6,7,8,9], we have developed a retrieval algorithm, which explicitly retrieves cloud properties together with other parameters such as atmospheric temperature, moisture, and trace gases profiles, surface skin temperature and emissivity. We will present results of testing the CrIMSS Environmental Data Record (EDR) operational algorithm and the LaRC CR method using IASI satellite data.…”
Section: Introductionmentioning
confidence: 99%